Road Geometric Design used AutoCAD® Civil 3D: A Case Study Jalan Campaka-Wanaraja Garut, Indonesia - Zulfa, Nabila; Rifai, Andri Irfan; Taufik, Muhammad (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The growth of road infrastructure has an essential role in economic growth in Indonesia. However, in its development, there needs to be more growth of vehicles and roads within the city. Road development is relatively slower than vehicle growth. One of the areas that experience congestion due to the imbalance of vehicle and road growth is the Campaka - Wanaraja road section. In this paper, a geometric design of the Campaka – Wanaraja road using the AutoCAD® Civil 3D method. The geometric design of this road is in the form of horizontal and vertical alignment. The geometric design of the Campaka – Wanaraja road aims to be safe and streamline the travel time of road users. The Result of the geometric design of the Campaka – Wanaraja road with a plan speed (VD) of 40 Km / h and the assumption of flat terrain is a horizontal alignment that has a curved radius plan (Rc) of 120 m and uses superelevation (e max ) 8%. This horizontal alignment consists of two horizontal plan arches, one full circle arch, and one Spiral-Circle-Spiral arch. In addition to horizontal alignment, a vertical alignment with an arch radius (L) of 200 m is also planned. Vertical alignment consists of a convex arch of seven pieces and a concave arch of six. In addition, the results of the calculation of the cut volume of 30,300,563.31 m3 and the fill volume of 255,154.40 m3 were obtained.